Wacana Pathetan - Bambang Sosodoro (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2006)
This study is based on the understanding that music has a number of similarities with language. The basic assumption is that people make music in the same way that people speak. This research is the experimental attempt to analyze music offavanese karawitan, in particular the rebab,from a linguistic approach, by choosing a study of discourse as one of the analytical tools. The study of musical discourse involves observing the rebaban in terms of its grammatical (internal) aspects, such as its musical patterns and techniques, and also its pragmatic (external) aspects, namely the musical role ofrebaban as applied to its context.A discourse is an expression and utterance in which one complete sentence with semantical and gramatical elements to attain intelligible sentence. Rebaban is one of expressive medium in karawitan. Using the perspective in linguistic, the complete meaningful expression is called a discourse. For that reason, expression of rebab can interact and communicate with other instruments (especially the main instruments) to form musical unity: this means that rebab also has musical discourse.Keywords:    Rebaban, Pathetan, Analitical Tools, Discourse